The causes, significance and consequences of inflammatory fibrosis in kidney transplantation: The Banff i‐IFTA lesion. Issue 2 (3rd January 2018) - Nankivell, Brian J.; Shingde, Meena; Keung, Karen L.; Fung, Caroline L‐S.; Borrows, Richard J.; O'Connell, Philip J.; Chapman, Jeremy R.
Abstract : Inflammation within areas of interstitial fibrosis and tubular atrophy (i‐IFTA) is associated with adverse outcomes in kidney transplantation. We evaluated i‐IFTA in 429 indication‐ and 2052 protocol‐driven biopsy samples from a longitudinal cohort of 362 kidney–pancreas recipients to determine its prevalence, time course, and relationships with T cell–mediated rejection (TCMR), immunosuppression, and outcome. Sequential histology demonstrated that i‐IFTA was preceded by cellular interstitial inflammation and followed by IF/TA. The prevalence and intensity of i‐IFTA increased with developing chronic fibrosis and correlated with inflammation, tubulitis, and immunosuppression era ( P < .001). Tacrolimus era–based immunosuppression was associated with reduced histologic inflammation in unscarred and scarred i‐IFTA compartments, ameliorated progression of IF, and increased conversion to inactive IF/TA (compared with cyclosporine era, P < .001). Prior acute (including borderline) TCMR and subclinical TCMR were followed by greater 1‐year i‐IFTA, remaining predictive by multivariate analysis and independent of humoral markers. One‐year i‐IFTA was associated with accelerated IF/TA, arterial fibrointimal hyperplasia, and chronic glomerulopathy and with reduced renal function ( P < .001 versus no i‐IFTA). In summary, i‐IFTA is the histologic consequence of active T cell–mediated alloimmunity, representing the interface between inflammation and tubular injury with fibrotic healing. Uncontrolled i‐IFTA is associated with adverse structural and functional outcomes. Abstract : This longitudinal cohort study concludes that i‐IFTA was the histological consequence of active T cell–mediated alloimmunity, representing the interface between inflammation and tubular injury, and followed by adverse structural and functional outcomes. See related articles on pages 293, 321, and 377 .